The role of inland waterway navigation in a sustainable transport system - Rohács, József; Simongáti, Győző (Transport, 2007)
Sustainable development has become a guiding principle of human activities nowadays. Sustainable transport can take a great part in future development. Today this is not the case, and road transport contributes to this above all. For sustainable transport development the necessity of modal shift is inevitable and the inland waterway navigation should get the higher share of the total transport where there is an alternative. This presentation shows the reasons why the inland waterway navigation can increase the level of sustainability.First Published Online: 27 Oct 2010